The Iron Supplementation Dose for Perinatal Iron Deficiency Differentially Alters the Neurochemistry of Frontal Cortex and Hippocampus in Adult Rats - Rao, Raghavendra (2012)
BACKGROUND: Long-term prefrontal cortex and hippocampus-based cognitive deficits are the sequelae of perinatal iron deficiency, despite iron supplementation starting in the newborn period. Whether high dose iron supplementation prevents these deficits is not known. METHODS: Perinatal iron deficiency was induced in rat pups using low-iron (3 mg/kg diet) diet during gestation until postnatal day (P) 8. Iron was supplemented using standard (40 mg/kg diet) or 10-fold higher (400 mg/kg diet) iron-containing diet until P21. Prefrontal cortex and hippocampal neurochemistry was determined using in vivo (1)H nuclear magnetic resonance spectroscopy at 9.4 tesla on P90. RESULTS: Both iron supplementation doses corrected anemia and brain iron deficiency by P21. The neurochemical profile of the prefrontal cortex in both supplementation groups was comparable to the control group. In the hippocampus, standard-dose iron supplementation resulted in lower N-acetylaspartate and phosphoethanolamine, and higher N-acetylaspartylglutamate and glycerophosphocholine + phosphocholine concentrations. High-dose iron supplementation resulted in lower phosphoethanolamine and higher glycerophosphocholine + phosphocholine concentrations. CONCLUSIONS: The iron supplementation dose for perinatal iron deficiency differentially alters the neurochemical profile of the prefrontal cortex and hippocampus in adulthood. The neurochemical changes suggest altered glutamatergic neurotransmission, hypomyelination and abnormal phospholipid metabolism in the formerly iron-deficient hippocampus.